2015
DOI: 10.1080/13607863.2015.1037244
|View full text |Cite
|
Sign up to set email alerts
|

Pain severity, interference, and prescription analgesic use among depressed, low-income homebound older adults

Abstract: The findings underscore the significant pain-related problems in these vulnerable individuals and the need for recognizing and treating both pain and depression more effectively using both pharmacologic and nonpharmacologic interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 64 publications
1
5
0
Order By: Relevance
“…We found that pain interference was positively associated with depression, which is consistent with previous studies of hemodialysis patients (56). It was recently reported that pain interference was more significantly associated with depression than pain intensity in cohorts with various pain issues (57,58), implying that with the appropriate assessment tool, pain interference can provide more useful information for healthcare workers. More specifically, patient-reported outcome measures of pain interference can help healthcare workers design personalized illness or symptom management programs (59).…”
Section: Discussionsupporting
confidence: 91%
“…We found that pain interference was positively associated with depression, which is consistent with previous studies of hemodialysis patients (56). It was recently reported that pain interference was more significantly associated with depression than pain intensity in cohorts with various pain issues (57,58), implying that with the appropriate assessment tool, pain interference can provide more useful information for healthcare workers. More specifically, patient-reported outcome measures of pain interference can help healthcare workers design personalized illness or symptom management programs (59).…”
Section: Discussionsupporting
confidence: 91%
“…21) Pain intensity and frequency have been repeatedly reported to be significantly associated with depression and this was also shown to be true in older adults. 22) The results show that the prevalence of signs and symptoms of TMD decrease with age. There were more patients with high disability in the 30-year-old age group.…”
Section: Discussionmentioning
confidence: 90%
“…Of those studies that used a framework ( n = 39, 58.2%), examples include Black feminist thought and critical arts-based inquiry, 35 participatory action research, 55 Gadamerian philosophical hermeneutics, 36 two nested hierarchical models (Bronfenbrenner’s bioecological model and social ecological model), 16 the National Institute on Aging Health Disparities Research Framework, 31 Newman’s theory, 48 the sociology of illness experience, 60 Rhodes’ risk environment framework, 61 Bronfenbrenner’s process–person–context–time model, 46 Neuman’s systems model, 62 the life course perspective, 45 and the biopsychosocial model. 28 , 30 , 32 , 43 , 63 , 64 We noted that studies that drew on theory offered more fulsome understandings of and approaches to marginalization, which sheds light on the structures underpinning aspects of chronic pain experiences among marginalized groups. For example, through the lens of Black feminist thought, Anthym 35 (p18) powerfully illuminates “the interlocking oppressions of race, gender, and class experienced by Black women” while “center[ing] alternative sources of knowledge, as well as alternative methods of knowledge validation.” Nevertheless, only a minority of studies clearly offered a theoretical view of the processes of marginalization.…”
Section: Resultsmentioning
confidence: 99%